Should healthcare providers do safety cases? Lessons from a cross-industry review of safety case practices. (April 2016) - Sujan, Mark A.; Habli, Ibrahim; Kelly, Tim P.; Pozzi, Simone; Johnson, Christopher W.
Highlights: Review of safety-case practice in UK industry and lessons for healthcare. Healthcare safety management systems may not support effective use of safety cases. Safety cases can support understanding and communication of risk. Education should be provided to healthcare providers and regulators. Research about effectiveness of safety cases is required. Abstract: Healthcare organisations are often encouraged to learn from other industries in order to develop proactive and rigorous safety management practices. In the UK safety–critical industries safety cases have been used to provide justification that systems are acceptably safe. There has been growing interest in healthcare in the application of safety cases for medical devices and health information technology. However, the introduction of safety cases into general safety management and regulatory practices in healthcare is largely unexplored and unsupported. Should healthcare as an industry be encouraged to adopt safety cases more widely? This paper reviews safety case practices in six UK industries and identifies drivers and developments in the adoption of safety cases. The paper argues that safety cases might best be used in healthcare to provide an exposition of risk rather than as a regulatory tool to demonstrate acceptable levels of safety. Safety cases might support healthcare organisations in establishing proactive safety management practices. However, there has been criticism that safety cases practices have, at times, contributed to poor safety management and standards by prompting a "tick-box" and compliance-driven approach. These criticisms represent challenges for the adoption of safety cases in healthcare, where the level of maturity of safety management systems is arguably still lower than in traditional safety–critical industries. Healthcare stakeholders require access to education and guidance that takes into account the specifics of healthcare as an industry. Further research is required to provide evidence about the effectiveness of safety cases and the costs involved with the approach.